Evaluation of the Influence of External Environmental Factors on Logistics Activities: Case Study of Ukrainian Retail Trade Enterprises - SHTAL, Tatyana V.; UVAROVA, Anastasiya; OSTAPENKO, Iuliia I. (Journal of Environmental Management and Tourism, 2019)
The article examines the influence of the external environment on the logistics activities of retail trade enterprises of Ukraine. External factors of logistics activities of retail trade enterprises, substantiated indexes of their evaluation were determined. The volume and composition of consumer demand, the development of the market of logistics services, efficiency of logistics activities and the state of competition in the retail market were analysed. Diagnosed the decrease in the efficiency of logistics activities of retail trade enterprises and the high level of its dependence on the factors of environment. The prospect of future research in this direction was formulated.